2020
DOI: 10.1038/s41598-019-57259-0
|View full text |Cite
|
Sign up to set email alerts
|

The Male Warrior Hypothesis: Testosterone-related Cooperation and Aggression in the Context of Intergroup Conflict

Abstract: The Male Warrior Hypothesis (MWH) establishes that men's psychology has been shaped by intergroup competition to acquire and protect reproductive resources. In this context, sex-specific selective pressures would have favored cooperation with the members of one's group in combination with hostility towards outsiders. We investigate the role of developmental testosterone, as measured indirectly through static markers of prenatal testosterone (2D:4D digit ratio) and pubertal testosterone (body musculature and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 75 publications
(103 reference statements)
3
26
0
1
Order By: Relevance
“…Evidence for the relationship between testosterone and many sexually dimorphic phenotypes spans several different areas of research (Björkqvist, 2018;Hoskin and Meldrum, 2018;Luoto et al, 2019a;Muñoz-Reyes et al, 2020). It is noteworthy that psychological research has not found reliably occurring differences in anger frequency; instead, sex differences have been found in verbal and physical aggression, both being higher in men (Archer, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the relationship between testosterone and many sexually dimorphic phenotypes spans several different areas of research (Björkqvist, 2018;Hoskin and Meldrum, 2018;Luoto et al, 2019a;Muñoz-Reyes et al, 2020). It is noteworthy that psychological research has not found reliably occurring differences in anger frequency; instead, sex differences have been found in verbal and physical aggression, both being higher in men (Archer, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on both humans and chimpanzees indicate an oxytocinergic system involvement during intergroup conflict [7,18]. It is widely believed that sports and games could closely imitate a real-life inter-group conflict and intra-group cohesion among humans [19]. It was therefore hypothesised that similar effect could also be visible shortly before participation in highly competitive games.…”
Section: Discussionmentioning
confidence: 99%
“…Human inter-group conflicts are part of our evolutionary history and success in such conflicts depends upon several adaptive mechanisms. Sports and games sometimes posit on humans a challenge situation that mimics inter-group conflict, as well as intra-group coordination to win over the opponent [19]. Sporting activities are very often chosen as a proxy to human combative situations.…”
Section: Introductionmentioning
confidence: 99%
“…Competition between groups (elective among males) would have contributed to determining the propensity of these males to remain within the group to which they belong at the period of mating, while the females, on the contrary, to migrate towards the husband’s group (Knipper et al, 2017 ). This greater propensity of males to feel part of a belonging group and to start a conflict with conspecifics of the outgroup is significantly correlated with testosterone production (Reimers and Diekhof, 2015 ; Muñoz-Reyes et al, 2020 ), which is extremely higher in males than in females. “[…] humans, particularly men, may possess psychological mechanisms enabling them to form coalitions capable of planning, initiating and executing acts of aggression on members of outgroups (with the ultimate goal of acquiring or protecting reproductive resources) ” (McDonald et al, 2012 , p. 671).…”
Section: From Vertebrates To Mammals Towards Homo Sapiens mentioning
confidence: 99%